The Role of Business Sustainability in the Financial Management Governance of Micro, Small, and Medium Enterprises in the Digital Era - Bryant Ritchie Trisnodjojo; Nirmadarningsih Hiya; Supiati; Renaldi; Nurnaningsih Utiarahman (Indonesian Journal Economic Review (IJER), 2026)
The purpose of this study is to explain the role of business sustainability in the financial management governance of micro, small, and medium enterprises in the digital era. This research employed a descriptive qualitative approach, with secondary data such as books and journal articles as references to aid analysis. The research results show that in the digital era, the concept of business sustainability is no longer merely a trend or a moral responsibility, but rather a strategic pillar that determines the life or death of micro, small, and medium enterprises. When integrated into financial management governance, sustainability serves as a navigator, ensuring that the use of digital technology not only pursues short-term profits but also long-term resilience. To survive and compete in the modern market, micro, small, and medium-sized enterprises are advised to immediately transition from manual financial record-keeping to digital-based systems such as smart accounting applications and integrated automated cashier platforms. This digitalization plays a crucial role because it provides full visibility of cash flow in real time, minimizes the risk of human error, and provides accurate data for rapid strategic decision-making.